Durable inequality - Tilly, Charles (University of California Press, 1998)
Charles Tilly, in this eloquent manifesto, presents a powerful new approach to the study of persistent social inequality. How, he asks, do long-lasting, systematic inequalities in life chances arise, and how do they come to distinguish members of different socially defined categories of persons? Exploring representative paired and unequal categories, such as male/female, black/white, and citizen/noncitizen, Tilly argues that the basic causes of these and similar inequalities greatly resemble one another.